Enhanced dielectric/ferroelectric properties of P(VDF-TrFE) composite films with organic perovskite ferroelectrics. (1st March 2023) - Li, Chaoyang; Cai, Yichen; Xie, Yongfa; Sheng, Chenxu; Qin, Yajie; Cong, Chunxiao; Qiu, Zhi-Jun; Liu, Ran; Hu, Laigui
Abstract: With excellent stability, flexibility, and piezoelectricity, poly(vinylidene fluoride) (PVDF) and its copolymer [P(VDF-TrFE)] have received much attention. However, the applications for its ferroelectricity still suffer the drawbacks of relative low remanent polarization ( P r ) and high coercive electric field ( E c ). In this work, P(VDF-TrFE) composite films were fabricated with the additive of organic perovskite ferroelectric MDABCO-NH4 I3 . Compared with pure P(VDF-TrFE), the P r increases from 7.17 to 12.7 μ C cm −2, while E c decreases from 516 to 324 kV cm −1 as well as increased permittivity from 15.6 to 37.0. These may provide an alternative way for ferroelectric memory, sensors, and energy storage devices.